Implementation of the principle individual approach to pupils of pre-schools - Nataliia Semenova; Kateryna Lukashchuk (Vasyl Stefanyk Precarpathian National University, 2017)
In the article the question of the principle of individual approach to studentskindergarten. We analyzed the normative - legal documents, a number of scientificapproaches to this problem. Also the implementation of effective forms of individual approachto preschool children in schools.Key words: individualization, individual approach, personality, ability.